Malaria : immune response to infection and vaccination - Mota, Maria M.; Rodriguez, Ana (Springer, 2017)
Currently, malaria kills more than 300,000 people per year, making it a top priority of world leaders and international organizations, who are working towards implementing and coordinating efforts to eradicate this disease. An effective malaria vaccine is recognized as the key element that will decide between success and failure in this fight. At present, despite intensive research efforts, such a vaccine is not yet available for use. However, there are a number of advanced candidate vaccines with high chances of success in the short term. Malaria: Immune Response to Infection and Vaccination provides a comprehensive view on the immune response to malaria and to the different vaccines under development. The book offers the following: - Contributions by top research leaders in the field, - Comparisons of the immune responses to both malaria infection and malaria vaccines, which are traditionally treated separately, - Coverage of the immune responses to the different stages of malaria, which are frequently treated as separate fields of resear.- Resumé vydavatel